Detoks Digital dan Otonomi Relasional pada peningkatan pemaknaan budaya kolektivitas - Hadi, Cholichul (Penerbit Goodwood, 2024)
Purpose: This study investigates how mandatory smartphone abstinence, framed as digital detox interventions, influences relational interdependence within collectivist cultural contexts. Specifically, it examines whether such interventions alter dyadic synchronization and emotional co-regulation, highlighting potential cultural moderation effects. Research Methodology: Using ecological momentary assessment (EMA) over a 14-day period, data were collected from 300 participants (150 dyads) in Japan and Indonesia. Dyadic adjustment was measured with the Dyadic Adjustment Scale, while physiological synchronization was assessed through heart rate variability (HRV) coherence using wearable devices. Comparisons were made before and after the digital detox period, and moderation by relational hierarchy and cultural background was analyzed. Results: Findings revealed that digital detox significantly increased face-to-face interaction time (d = 1.2, p < 0.001). However, paradoxically, physiological synchronization decreased in hierarchical relationships such as parent–child (? = ?0.45, p = 0.02). Strong cultural moderation effects were observed, with collectivist norms shaping both behavioral and physiological outcomes. Conclusions: Although digital detox policies can enhance direct social engagement, they may unintentionally disrupt non-verbal interdependence in relational contexts characterized by hierarchy. This suggests that blanket digital disconnection strategies may not universally support relational health. Limitations: The study relied on short-term interventions and culturally specific samples (Japan and Indonesia), limiting generalizability. Longer longitudinal studies are needed. Contribution: This research provides the first cross-cultural neuroscientific evidence that disconnection policies may undermine implicit forms of relational interdependence, underscoring the need for culturally sensitive guidelines.